Wearable microneedle graphene field-effect transistor sensors - Holicky,M; Fenech-Salerno,B; Dabas,R; Teenan,O; Li,X; Steer,IV; Higgins,C; Akhavani,M; Gadegaard,N; Kamaly,N; Cass,A; Torrisi,F (2D Materials, 2025)
Continuous monitoring of biomarkers in interstitial fluid (ISF) holds great potential for early disease detection and personalized medicine.This work presents a novel biosensing platform that combines microneedle technology with graphene field-effect transistors (GFETs) toenable sensitive, continuous analyte detection directly in ISF. Using spray-coating and laser lithography techniques, we create GFET channels on three-dimensional microneedle tips. The resulting devices show characteristic GFET behavior in solution. As a proof-of-concept, we demonstrate pH sensing capabilities with a sensitivity of 2.50% ID/pH and the ability to detect changes as small as 0.04pH units. Crucially, we show that these microneedle GFETs can function when inserted into ex-vivo human skin samples, with GFETgating occurring through the skin tissue. Finally, based on MTT assays and cellular imaging, no cytotoxic effect was observed which is animportant prerequisite for human use.